GROUNDWATER CHEMISTRY OF SPRINGS IN THE SOUTHERN SLOPE OF MERAPI VOLCANO, SLEMAN REGENCY, YOGYAKARTA SPECIAL REGION, INDONESIA - , Boulom, Johnny ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Springs are easily found in the southern slope of Merapi volcano, Sleman Regency. Most of springs appear at the river bank and there are many springs according the secondary data in the area that might be located in different morphology and lithology, which might have different hydrogeology and hydrology setting. In response to the above issue, the study of groundwater chemistry and groundwater quantity are carried out. The main objectives of this research are to recognize the characteristics of springs by field observation and in-situ measurement of springs discharge, Electric-conductivity, and Temperature in rainy and dry season, also determined the relationship of springs based on their chemical composition, and estimated the recharge rate in the study area. The twelve (12) spring samples were taken in the upper, middle, and lower part of study area. According to Kurlov and Piper diagram methods, the chemical composition of 12 spring samples almost similar and did not significantly different for most properties from upstream to downstream, which are Na-Ca-HCO3 to Na-Ca-HCO3-SO4, only one spring sample call Jatiningsih has different chemical composition Ca-Na-Mg-HCO3 with other eleven (11) springs. To understand the relationship of twelve (12) spring water chemistry composition was displayed by Fingerprint, Composition, and Stiff Pattern diagrams. Consequently, based on the chemical composition of twelve (12) spring samples and the type of lithology in the study area, the springs can be divided into three groups. Group 1, there are ten (10) spring samples which have similar chemical composition and the source influence by Merapi Aquifer System which consist of Sleman and Yogyakarta formations, indicated that springs in group 1 are hydraulically interconnected. Group 2, Umbul Pajangan spring, has similar chemical composition with springs in group1. However it has high ionic concentration than ten (10) spring samples in group1. The source may be come from deep aquifer (Sleman Formation), and is not hydraulically interconnected to other springs. Group 3, Jatiningsih spring has significantly different ionic composition with other eleven (11) springs in group 1 and 2. This spring located in the west side of study area, the source may influence by groundwater from Sentolo formation, which consist of limestone and has high Ca-HCO3 concentration, indicated that this spring is not hydraulically interconnected to other eleven (11) springs. Based on chloride concentration in springs and precipitation from upstream to downstream, also the annual rainfall data, the estimation of groundwater recharge by using Chloride Mass Balance method was done in this research area and the amount of groundwater recharge was estimated is 490 mm/year for whole area of research, and showing a good correlation when compare with previous research.